A genetically targeted reporter for PET imaging of deep neuronal circuits in mammalian brains. (12th October 2021) - Shimojo, Masafumi; Ono, Maiko; Takuwa, Hiroyuki; Mimura, Koki; Nagai, Yuji; Fujinaga, Masayuki; Kikuchi, Tatsuya; Okada, Maki; Seki, Chie; Tokunaga, Masaki; Maeda, Jun; Takado, Yuhei; et al.
Abstract: Positron emission tomography (PET) allows biomolecular tracking but PET monitoring of brain networks has been hampered by a lack of suitable reporters. Here, we take advantage of bacterial dihydrofolate reductase, ecDHFR, and its unique antagonist, TMP, to facilitate in vivo imaging in the brain. Peripheral administration of radiofluorinated and fluorescent TMP analogs enabled PET and intravital microscopy, respectively, of neuronal ecDHFR expression in mice. This technique can be used to the visualize neuronal circuit activity elicited by chemogenetic manipulation in the mouse hippocampus. Notably, ecDHFR‐PET allows mapping of neuronal projections in non‐human primate brains, demonstrating the applicability of ecDHFR‐based tracking technologies for network monitoring. Finally, we demonstrate the utility of TMP analogs for PET studies of turnover and self‐assembly of proteins tagged with ecDHFR mutants. These results establish opportunities for a broad spectrum of previously unattainable PET analyses of mammalian brain circuits at the molecular level. SYNOPSIS: ecDHFR‐based reporter system can be utilized for bimodal fluorescence and Positron emission tomography (PET) imaging of expression and dynamics of its fused protein of interest in living animal brains, offering broad‐spectrum analyses of a mammalian deep brain circuit at molecular levels. We established a genetically encoded ecDHFR‐based reporter system applicable for bimodal optical and PET imaging in living animal brains. The reporter gene expression driven by an activity‐dependent promoter illuminates neuronal ensemble activities elicited by chemogenetic manipulation in the mouse hippocampal circuit. ecDHFR/TMP systems enable visualization of neuronal tracts in deep brain regions of non‐human primates. The utility of TMP analogs for PET monitoring of aggregation and turnover of proteins tagged with mutant forms of ecDHFR. Abstract : Application of bacterial dihydrofolate reductase ecDHFR and its unique antagonist TMP achieves a broad spectrum of previously unattainable in vivo PET analyses of mammalian brain circuits at the molecular level.